An observational study of changes in corneal parameters following use of soft contact lens and rigid gas permeable lens - Chandrakar, Neha; Patel, Ohm Vrajlal; Mahajan, Sonam; Bajaj, Piyush (Asian Journal of Medical Sciences, 2017)
Background: There have been significant advancements in contact lens designs and materials over the past few decades, the lenses still represent a foreign body in the ocular environment and may lead to physiological (corneal oedema or thinning) as well as mechanical (on corneal curvature) effects on the eye.As there are not many studies reporting the effect of contact lens on eyes in Indian population, this study was designed to fill the lacunae of knowledge in this context. Aims and Objective: To evaluate and compare the change in anterior central corneal curvature & central corneal thickness following use of soft contact lens (silicon-hydrogel) and Rigid Gas Permeable (fluoropolymer) contact lens. Materials and Methods: It was a Prospective, Observational, Comparative study Conducted at Venu Eye Institute & Research Centre, New Delhi. Forty eyes of 21 subjects who required contact lens were included in two groups: 20 eyes in group A (RGP contact lens users) and 20 eyes in group B (Soft contact lens users). A “baseline” parameters was measured prior to contact lens use & changes associated with contact lens wear was considered in relation to the normal baseline parameters when followed up at 3 and 6 months. Results: The Change in anterior central corneal curvature in both the groups was NOT statistically significant (p-value of >0.05) between pre-contact lens wear and with contact lens wear at 3 & 6 months. And, there was Significant Corneal thinning between pre-contact lens wear and with contact lens wear at 3 & 6 months in both the groups individually (p-value <0.05). However, on comparing the difference in change in CCT between both the groups was NOT statistically significant at 3 and 6 months. Conclusions: With contact lens use, there was no significant change in Anterior Central Corneal Curvature in Soft as well as RGP contact lens group at 3 & 6 months. Though there was significant central corneal thinning in both the groups individually at 3 & 6 months, However, on comparing the change in CCT between both the groups at 3 and 6 months was NOT significant. Asian Journal of Medical Sciences Vol.8(5) 2017 70-74